Clinacanthus nutans: Its potential against diabetic vascular diseases - Ahmad Khusairi Azemi; Siti Safiah Mokhtar; Aida Hanum Ghulam Rasool (Universidade de São Paulo, 2021)
Diabetes is an independent risk factor for the development of cardiovascular disease, with approximately 80% of cardiovascular mortality and morbidity linked to vascular complications such as atherosclerosis. It has been estimated that up to one-third of patients with diabetes mellitus use some form of complementary and/or alternative medicine. One plant that has received attention from diabetic patients for its perceived antidiabetic properties is Clinacanthus nutans, a member of the Acanthaceae family that is known as snake grass. Ethnomedical applications of this herb have been identified for the treatment of certain conditions, including fever, diabetes, skin rashes, and insect bites. This review aims to assess the potential of C. nutans to be used in the prevention and/or treatment of diabetic vasculopathy. Evidence for antidiabetic, anti-inflammatory, and dyslipidemic properties of C. nutans, as shown from experimental studies, is presented and discussed. Diabetes, inflammation, and hyperlipidemia are known to play significant roles in the initiation and severity of diabetic cardiovascular disease; thus, targeting these factors might be beneficial for preventing and/or treating diabetic vasculopathy.